N / O / P co-doped porous carbon material and preparation method and application thereof
By introducing N/O/P co-doped porous carbon structure into hard carbon materials, the problem of insufficient sodium ion storage performance at low potentials is solved, and rapid storage and high cycle stability of sodium at high potentials is achieved.
Patent Information
- Application Number
- CN202411518003.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-10-29
AI Technical Summary
The existing hard carbon materials have low sodium ion storage performance at low potentials, slow kinetics, and safety hazards at high rates, making it difficult to achieve rapid sodium storage at high potentials.
Using N/O/P co-doped porous carbon material, the crosslinking of polysaccharides and phosphooxylate is carbonized at low temperature, and rich phosphooxy groups are introduced, expand the distance between carbon layers, increase the active sites, and improve the adsorption of sodium ions and Diffusion capability.
It has achieved excellent reversible specific capacity and high cycle stability under high current density, and improved the kinetic performance and safety of the negative electrode material of sodium ion battery.
Smart Images

Figure CN119400858A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion battery / capacitor negative electrode materials, and specifically relates to a N / O / P co-doped porous carbon material and a preparation method and application thereof. Background Art
[0002] Among the various negative electrode materials currently being studied, carbon materials have attracted much attention due to their low cost, excellent performance, and simple preparation. Currently, the research on carbon materials mainly focuses on graphite and amorphous carbon. Graphite is a sp 2 Hybrid ordered carbon has a crystalline hexagonal structure of graphene stacked along the c-axis; amorphous carbon is non-crystalline and can be divided into soft carbon and hard carbon according to whether it is easy to undergo graphitization transformation at high temperature. Hard carbon has been widely used and is the most promising sodium storage anode material because of its local microcrystalline structure and large interlayer spacing. At a lower potential (0-0.1V vs. Na / Na + ) can release a large reversible capacity. However, the low potential (0-0.1V vs.Na / Na + ) is a diffusion-controlled process, which is subject to slow kinetics that limit rate performance, and the low voltage near the sodium plating may cause safety issues, especially at high rates. + The carbon anode for intercalation and deintercalation should promote the + ) Rapid storage mechanism of sodium.
[0003] Heteroatom doping can expand the path of ion transport and shorten the distance of ion transmission. It is an effective strategy to improve the kinetics of carbon materials. Studies have shown that heteroatom doping (such as N, S, B and P) of carbon materials has the following advantages: (1) Expanding the interlayer spacing and reducing Na + (1) increase the diffusion impedance during the charge and discharge process, and enhance the wettability of the electrolyte to the carbon material; (2) increase the surface groups of the carbon material, providing more active sites for reversible absorption and desorption of sodium; (3) improve the specific capacity of the carbon material under high current. However, the temperature for preparing conventional hard carbon materials is generally high (>1300℃), and the energy consumption is large. Based on this, the development of hard carbon negative electrode materials for preparing high-rate sodium ion batteries / sodium ion capacitors under low temperature conditions has become the focus of current research.
[0004] Patent CN202311412874.3 discloses a method for preparing a low-temperature synthesized high-rate sodium ion battery hard carbon negative electrode material. The disclosed preparation method has a complex process. When the prepared hard carbon material is used as the negative electrode of a sodium ion battery, its high-rate performance is relatively low and needs to be improved. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing N / O / P co-doped porous carbon material in view of the above-mentioned deficiencies in the prior art.
[0006] To achieve the above object, the present invention adopts the following technical solution:
[0007] The first object of the present invention is to provide a N / O / P co-doped porous carbon material, which contains nitrogen-containing groups and phosphorus-containing groups through elemental analysis, wherein the nitrogen-containing groups include pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and nitrogen oxides, and the phosphorus-containing groups include C3-P=O, CPO and COP, wherein the N content ranges from 10 to 15wt.%, the O content ranges from 24 to 40wt.%, and the P content ranges from 1 to 10wt.%.
[0008] In this embodiment, the nitrogen-containing groups (pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and nitrogen oxides) and phosphorus-containing groups (C3-P=O, CPO, COP) of the N / O / P co-doped porous carbon material can promote the sodium ion transport by changing the electronic structure of the carbon material, providing more active sites for reversible adsorption and desorption of sodium, and improving the wettability of the carbon material. The present invention finds that the contents of N, O and P elements range from 10 to 15 wt.%, 24 to 40 wt.%, and 1 to 10 wt.%, respectively. At this time, the specific surface area of the carbon material is 44 to 227 m 2 g -1 , the surface functional group content is within an appropriate range, and the carbon material has excellent reversible specific capacity at high current density and high cycle stability.
[0009] Furthermore, the interlayer spacing d(002) of the graphite (002) crystal plane was measured by X-ray diffraction to satisfy: 0.39nm <d(002)<0.43nm。
[0010] Furthermore, the specific surface area SSA was measured by nitrogen adsorption and desorption to meet the following requirements: 44 m 2 / g<SSA<227m 2 / g.
[0011] Furthermore, the mass percentages of the elements in the N / O / P co-doped porous carbon material are: C content ranges from 35 to 65 wt.%, N content ranges from 10 to 15 wt.%, O content ranges from 24 to 40 wt.%, and P content ranges from 1 to 10 wt.%.
[0012] The second object of the present invention is to provide a method for preparing the above-mentioned N / O / P co-doped porous carbon material, comprising the following steps:
[0013] S1, mixing a polysaccharide, a cross-linking agent and deionized water, stirring evenly to obtain a mixed solution, wherein the molar ratio of the amino group in the polysaccharide to the phosphate group in the cross-linking agent is 1: (1-6);
[0014] S2, drying the mixed solution obtained in step S1 to obtain a precursor;
[0015] S3, placing the precursor obtained in step S2 in an inert atmosphere and heating it to 600-800° C. for carbonization, then grinding and washing the obtained black powder with hot water, and drying to obtain the final products.
[0016] It should be noted that:
[0017] The polysaccharide described in step S1 is a polysaccharide that is easier to disperse and cross-link with phosphate groups. The doped nitrogen comes from the polysaccharide, and the doped phosphorus mainly comes from the cross-linking agent. The molar ratio of amino group to phosphate group must be 1: (1-6).
[0018] In step S1, the drying environment is not limited, as long as the solvent in the sample is completely removed;
[0019] The carbonization environment in step S3 is an inert atmosphere which may be nitrogen, argon, helium, etc., and the gas flow rate may be controlled at 0.1-20 mL / min.
[0020] The preparation method adopts a low-temperature carbonization treatment, that is, the temperature is programmed to rise to 600-800°C for carbonization, which is conducive to the active groups of the polysaccharide acting as anchoring points for cross-linking with phosphocyanate groups, and in-situ doping to obtain a N / O / P co-doped carbon negative electrode. By changing the amount of the cross-linking agent, the microstructure and surface chemical state of the carbon material are adjusted to obtain a carbon negative electrode with rapid sodium storage behavior.
[0021] Furthermore, in step S2, the drying operation is specifically performed at 60-65° C. for 6-8 hours.
[0022] Furthermore, in step S3, the rate of the programmed temperature increase is 3-5°C / min, and after the temperature reaches 600-800°C, the temperature is maintained at a constant level for 2h-3h for carbonization.
[0023] Furthermore, the polysaccharide includes any one of polysaccharides containing amino groups such as chitosan oligosaccharide, glucosamine, chitosan or chitin.
[0024] Furthermore, the cross-linking agent includes any one of phosphates such as sodium hexametaphosphate, sodium tripolyphosphate, sodium pyrophosphate, trisodium phosphate, disodium hydrogen phosphate or sodium dihydrogen phosphate.
[0025] The third object of the present invention is to provide the use of the above-mentioned N / O / P co-doped porous carbon material in the preparation of anode materials for sodium ion batteries.
[0026] The fourth object of the present invention is to provide a sodium ion battery, comprising a sodium ion battery negative electrode material prepared using the above-mentioned N / O / P co-doped porous carbon material.
[0027] The fifth object of the present invention is to provide a sodium ion capacitor comprising positive and negative electrode sheets, wherein the negative electrode material of the sodium ion capacitor comprises the negative electrode material obtained by pre-sodiumizing the above-mentioned N / O / P co-doped porous carbon material.
[0028] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0029] (1) The present invention provides a N / O / P co-doped porous carbon material. The material is designed from the molecular scale, and the active groups of polysaccharides such as chitosan oligosaccharides are used as anchoring points to cross-link with phosphodiesterases. During the low-temperature carbonization process, abundant phosphodiesterases are introduced in situ to obtain a N / O / P co-doped carbon negative electrode. The introduction of N / O / P can not only improve the electronegativity of the material, but also expand the distance between the carbon layers, generate a large number of defects, and achieve Na + During the pyrolysis process, the decomposition of phosphorus-containing substances gives the carbon material a rich pore structure, which can provide a large number of active sites to act as Na + Buffer reservoir, thereby effectively enhancing ion diffusion kinetics. By changing the amount of phosphate ions, the microstructure and surface chemical state of the carbon material are adjusted to obtain a carbon negative electrode with rapid sodium storage behavior.
[0030] (2) The N / O / P co-doped carbon anode prepared by the present invention has better electrochemical performance than commercial hard carbon. -1 The reversible capacity is as high as 225.8 mAh g -1 , even at 10A g -1 It also maintains good rate performance (91.4 mAh g -1 ), at 2A g -1 After 1000 cycles at a current density of 142.1 mAh g -1 The reversible specific capacity of the material was 99.9%, and the coulombic efficiency was maintained at 99.9%. The material was assembled into a sodium ion capacitor with activated carbon prepared by the research group, which was -1 The energy density is as high as 105.2Wh kg -1 The preparation method is simple, the cost is low and the efficiency is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a comparison of infrared spectra of the precursors prepared in Example 1-Example 3;
[0032] Figure 2 TEM image of sample COSP6-3-600 prepared in Example 2;
[0033] Figure 3 Mapping diagram of sample COSP6-3-600 prepared in Example 2;
[0034] Figure 4 XRD comparison diagram of samples prepared in Example 1 to Example 3;
[0035] Figure 5 Nitrogen adsorption / desorption isotherms and pore size distribution diagrams of samples prepared in Examples 1 to 3;
[0036] Figure 6 This is the XPS graph of the sample COSP6-3-600 prepared in Example 3;
[0037] Figure 7 This is a comparison chart of the rate performance of samples prepared in Examples 1 to 3;
[0038] Figure 8 The sample COSP6-3-600 prepared in Example 3 was -1 Cycle performance diagram below;
[0039] Fig. 9 The rate performance diagram of the sample COSP6-3-600 prepared in Example 3 and commercial hard carbon;
[0040] Fig.10 It is a comparison diagram of the rate performance of the sample CSCP6-1-600 prepared in Example 3 and the sample COSP6-1-600 prepared in Comparative Example 1;
[0041] Fig.11 This is the electrochemical performance diagram of the sodium ion capacitor assembled with COSP6-3-600 as the negative electrode material and the existing carbon positive electrode in Example 3. DETAILED DESCRIPTION
[0042] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific test method, instrument or condition is specified in the examples, it is carried out according to the technology or condition described in the literature in this field or according to the product instructions. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0043] Example 1
[0044] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0045] Weigh 2g of chitosan oligosaccharide, and then weigh a certain amount of sodium hexametaphosphate according to the molar ratio of amino group to phosphate group of 1, respectively, mix them into a certain volume of deionized water solution, stir magnetically at room temperature for 2h, and the obtained complex is first dried in a 65℃ forced air drying oven for 6h and then transferred to a vacuum drying oven for drying for 6h, and then the dried precursor is placed in a tubular furnace under Ar protection for carbonization, and the heating rate is 5℃min -1 The carbonization temperature range was set at 600 °C, and the holding time was 2 h. After carbonization, the obtained black powder was ground and washed with hot water, and then transferred to a 65 °C oven to be fully dried for 24 h. The obtained materials were named COSP6-1-600.
[0046] Example 2
[0047] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0048] It is basically the same as Example 1, except that the molar ratio of amino group to phosphate group is 3. The prepared material is named COSP6-3-600.
[0049] Example 3
[0050] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0051] It is basically the same as Example 1, except that the molar ratio of amino group to phosphate group is 6. The prepared material is named COSP6-6-600.
[0052] Example 4
[0053] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0054] It is basically the same as Example 2, except that the carbonization temperature range is set at 700° C. and the prepared material is named COSP6-3-700.
[0055] Example 5
[0056] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0057] It is basically the same as Example 2, except that the carbonization temperature range is set at 800° C. and the prepared material is named COSP6-3-800.
[0058] Example 6
[0059] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0060] The method is basically the same as Example 1, except that the polysaccharide providing amino groups is chitosan hydrochloride, and the prepared material is named CSCP6-1-600.
[0061] Example 7
[0062] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0063] The method is basically the same as Example 1, except that the polysaccharide providing amino groups is glucosamine, and the prepared material is named glucosamine-1-600.
[0064] Example 8
[0065] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0066] The method is basically the same as Example 1, except that the polysaccharide providing amino groups is chitosan, and the prepared material is named chitosan-1-600.
[0067] Example 9
[0068] This embodiment provides a method for preparing a N / O / P co-doped porous carbon material.
[0069] The method is basically the same as Example 1, except that the cross-linking agent is selected from sodium tripolyphosphate, sodium pyrophosphate, trisodium phosphate, disodium hydrogen phosphate or sodium dihydrogen phosphate.
[0070] Comparative Example 1
[0071] This embodiment provides a method for preparing a carbon material.
[0072] It is basically the same as Example 1, except that sodium hexametaphosphate is not added, and the prepared carbon material is named COS-600.
[0073] Performance characterization:
[0074] The N / O / P co-doped porous carbon materials prepared in Examples 1 to 9 all have similar microscopic morphologies and physicochemical characteristics, and contain nitrogen-containing groups and phosphorus-containing groups, wherein the nitrogen-containing groups include pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and nitrogen oxides, and the phosphorus-containing groups include C3-P=O, CPO and COP, wherein the N content ranges from 10 to 15 wt.%, the O content ranges from 24 to 40 wt.%, and the P content ranges from 1 to 10 wt.%. In the study, it was found that the carbonization temperature has a great influence on the electrochemical properties of the N / O / P co-doped porous carbon material of the present invention. The present invention finds that when the carbonization temperature is 600°C, the electrochemical properties of the N / O / P co-doped porous carbon material are better. The following is a detailed description of Examples 1-3 as examples:
[0075] refer to Figure 1 , which is a comparison of the infrared spectra of the precursors prepared in Examples 1 to 3; the appearance of the P=O characteristic peak indicates that sodium hexametaphosphate is successfully cross-linked to chitosan oligosaccharide. After cross-linking, the disappearance of the NH bending vibration peak and the shift of the CN characteristic peak indicate that the amino group of chitosan oligosaccharide (COS) is ionically cross-linked with the phosphate group of sodium hexametaphosphate.
[0076] refer to Figure 2 , which is a TEM (high resolution transmission electron microscope) image of the sample COSP6-3-600 prepared in Example 2; it can be seen that the microstructure of the sample is long-range disorder, some of which are nanoscale pores, and short-range ordered graphite carbon layers with an interlayer spacing of about 0.424nm.
[0077] Reference Figure 3 , is the mapping (scanning electron microscope energy spectrum scan) image of the sample COSP6-3-600 prepared in Example 2; it can be seen that the sample has achieved uniform doping of heteroatoms nitrogen, oxygen and phosphorus. The present invention analyzes and obtains that the mass percentages of each element in the N / O / P co-doped porous carbon material are: C content ranges from 35 to 65wt.%, N content ranges from 10 to 15wt.%, O content ranges from 24 to 40wt.%, and P content ranges from 1 to 10wt%.
[0078] Reference Figure 4 , which is a comparison chart of XRD (X-ray diffraction analysis) of the samples prepared in Example 1 to Example 3; it can be seen that the COSP6-3-600 sample has the largest interlayer spacing of graphite crystallites, among which the interlayer spacing of the (002) crystal plane of the COSP6-1-600 sample is d(002)=0.395nm, the interlayer spacing of the (002) crystal plane of the COSP6-3-600 sample is d(002)=0.431nm, the interlayer spacing of the (002) crystal plane of the COSP6-6-600 sample is d(002)=0.391nm, and the interlayer spacing of the (002) crystal plane of the comparative example COS-600 sample is d(002)=0.388nm.
[0079] Reference Figure 5 , which are nitrogen adsorption / desorption isotherms and pore size distribution diagrams of the samples prepared in Examples 1 to 3; it can be seen that the hierarchical pore structure of the samples, the specific data are shown in Table 1.
[0080] Table 1.
[0081]
[0082] refer to Figure 6, which is the XPS (X-ray photoelectron spectroscopy) diagram of the sample COSP6-3-600 prepared in Example 3; the characteristic peaks of C1s, N1s, O1s and P2p can be observed in the full spectrum, confirming the coexistence of carbon, nitrogen, oxygen and phosphorus in the sample.
[0083] refer to Figure 7 , which is a comparison chart of the rate performance of the samples prepared in Example 1 to Example 3; it can be seen that the samples have excellent rate performance, COSP6-3-600 at 0.1A g -1 The reversible capacity is as high as 225.8 mAh g -1 , even at 10A g -1 It also maintains good rate performance (91.4 mAh g -1 ).
[0084] refer to Figure 8 , COSP6-3-600 prepared in Example 3 at 2A g -1 Cyclic performance diagram under 2A g -1 After 1000 consecutive cycles at a current density of 142.1 mAh g -1 The reversible specific capacity has a high coulombic efficiency (99.9%).
[0085] refer to Fig. 9 , which is a rate performance diagram of the sample COSP6-3-600 prepared in Example 3 and commercial hard carbon. It can be seen that the rate performance of the COSP6-3-600 sample is better than that of the commercial hard carbon.
[0086] refer to Fig.10 , which is a comparison diagram of the rate performance of sample CSCP6-1-600 prepared in Example 3 and sample COSP6-1-600 in Comparative Example 1.
[0087] Example 10
[0088] In this embodiment, the nitrogen / oxygen / phosphorus co-doped carbon negative electrode in Example 3 and the existing carbon positive electrode are assembled into a sodium ion capacitor.
[0089] The battery was assembled in a glove box with a high-purity argon atmosphere using a CR2016 button shell. In the assembled half-cell system, the prepared electrode was used as the working electrode, the corresponding metal sodium was used as the counter electrode, the glass fiber was used as the diaphragm, and 1MNaClO4 (EC / DEC, 1 / 1 vol.%) was used as the electrolyte. The battery was assembled in the order of negative electrode shell-sodium sheet-diaphragm-electrolyte-electrode sheet (COSP6-3-600)-gasket-spring-positive electrode shell, and then the negative electrode shell was placed upwards for battery packaging using a tablet press. The battery was left to stand for 6 hours to wait for the electrolyte to be completely infiltrated before electrochemical testing was performed at 0.1A g -1After 10 cycles under the current density condition, it was finally discharged to about 0.01V, keeping the negative electrode in the pre-metallized state. In addition, the disassembly of the half-cell and the assembly of the sodium ion capacitor were completed in the glove box. The sodium ion capacitor was assembled in the order of negative electrode shell-pre-sodiumized COSP6-3-600-diaphragm-electrolyte-positive electrode sheet-gasket-spring-positive electrode shell.
[0090] like Fig.11 As shown, this is an electrochemical performance diagram of a sodium ion capacitor assembled with COSP6-3-600 as the negative electrode material and an existing carbon positive electrode in Example 3. It can be seen that the dual-carbon sodium ion capacitor assembled with COSP6-3-600 as the negative electrode and activated carbon (KC4) as the positive electrode has excellent energy density and power density.
[0091] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0092] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A N / O / P co-doped porous carbon material, characterized in that: The N / O / P co-doped porous carbon material contains nitrogen-containing groups and phosphorus-containing groups through elemental analysis, wherein the nitrogen-containing groups include pyridinic nitrogen, pyrrolic nitrogen, graphitic nitrogen and nitrogen oxides, and the phosphorus-containing groups include C3-P=O, CPO and COP, wherein the N content ranges from 10 to 15 wt.%, the O content ranges from 24 to 40 wt.%, and the P content ranges from 1 to 10 wt.%.
2. The N / O / P co-doped porous carbon material according to claim 1, characterized in that: The interlayer spacing d(002) of the (002) crystal plane measured by X-ray diffraction satisfies: 0.39nm <d(002)<0.43nm。 3. The N / O / P co-doped porous carbon material according to claim 1, characterized in that: The specific surface area SSA measured by nitrogen adsorption and desorption satisfies: 44m 2 / g<SSA<227m 2 / g.
4. The N / O / P co-doped porous carbon material according to claim 1, characterized in that: The mass percentages of the elements in the N / O / P co-doped porous carbon material are as follows: C content ranges from 35 to 65 wt.%, N content ranges from 10 to 15 wt.%, O content ranges from 24 to 40 wt.%, and P content ranges from 1 to 10 wt.%.
5. A method for preparing the N / O / P co-doped porous carbon material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, mixing a polysaccharide, a cross-linking agent and deionized water, stirring evenly to obtain a mixed solution, wherein the molar ratio of the amino group in the polysaccharide to the phosphate group in the cross-linking agent is 1: (1-6); S2, drying the mixed solution obtained in step S1 to obtain a precursor; S3, placing the precursor obtained in step S2 in an inert atmosphere and heating it to 600-800° C. for carbonization, then grinding and washing the obtained black powder with hot water, and drying to obtain the final products.
6. The preparation method according to claim 5, characterized in that: In step S2, the drying operation is performed at 60-65°C for 6-8h; in step S3, the rate of the programmed temperature increase is 3-5°C min -1 , then heat to 600-800℃ and keep the temperature constant for 2h-3h for carbonization.
7. The preparation method according to claim 5, characterized in that: The polysaccharide includes any one of amino-containing polysaccharides such as chitosan oligosaccharide, glucosamine, chitosan or chitin; the crosslinking agent includes any one of phosphate-containing salts such as sodium hexametaphosphate, sodium tripolyphosphate, sodium pyrophosphate, trisodium phosphate, disodium hydrogen phosphate or sodium dihydrogen phosphate.
8. Use of the N / O / P co-doped porous carbon material according to any one of claims 1 to 4 in preparing negative electrode materials for sodium ion batteries.
9. A sodium ion battery, characterized in that: The invention comprises a negative electrode material for a sodium ion battery prepared by using the N / O / P co-doped porous carbon material as described in any one of claims 1 to 4.
10. A sodium ion capacitor comprising positive and negative electrode sheets, characterized in that: The negative electrode material of the sodium ion capacitor includes a negative electrode material obtained by pre-sodiumizing the N / O / P co-doped porous carbon material according to any one of claims 1 to 4.
Citation Information
Patent Citations
Preparation method of high-rate sodium-ion battery hard carbon negative electrode material synthesized at low temperature
CN117416948A
Preparation method of heteroatom-doped multi-stage hole carbon material, and application in lithium battery cathode slurry
CN110504450A
Nitrogen and phosphorus co-doped sodium ion battery hard carbon negative electrode material and preparation method thereof
CN116534839A
Nitrogen, phosphorus and oxygen in-situ co-doped porous carbon material as well as preparation method and application thereof
CN117877893A
Manufacturing method for carbon complex structure comprising hetero elements and carbon complex structure using same
KR1020140092506A